Predicting Attitudes Towards Marital Infidelity Based on Marital Conflict and Marital Quality Among Women - Pourmolaie, Shayan; Sazesh Rahbarjou, Seyedeh Sanaz; Shamsaldini, Ahmad (Psychology of Woman Journal, 2023)
Objective: Marital infidelity is one of the most significant threats to the stability and continuity of marriage and refers to any sexual or emotional relationship beyond the committed relationship between two spouses. The current research was conducted to determine the relationship between marital conflict and marital quality with attitudes towards marital infidelity.Methods and Materials: This descriptive-correlational study involved all married women visiting counseling centers in Tonekabon city during the first six months of the year 2023, from which a sample of 118 participants was selected. The research instruments included: the Attitude Towards Marital Infidelity Scale by Mark Whatley (2006), the Marital Conflict Scale by Barati and Sanaei (1996), and the Marital Quality Scale by Busby et al. (1995). Data analysis was performed using correlation and regression analysis methods with the aid of SPSS version 23 software.Findings: The results showed a significant positive relationship between marital conflict and attitudes towards marital infidelity (r = 0.42, p < 0.001). The results also indicated a significant negative correlation between marital quality and attitudes towards marital infidelity (r = -0.33, p < 0.001).Conclusion: It can be concluded that there is a relationship between marital conflict and marital quality with attitudes towards marital infidelity.